Household preparedness for emergency events: a cross-sectional survey on residents in four regions of China - Chaojie Liu; Wei Xu; Chao Yi Chen; Yajun Dai; Weilan Xu; Qunhong Wu; Yanhua Hao; Ning Ning (BMJ Open)
Objective This study aimed to assess household preparedness for emergency events and its determinants in China.Design A cross-sectional questionnaire survey was conducted on 3541 households in China in 2015.Participants Households were selected using a stratified cluster sampling strategy, representing central, eastern, western and southern regions of China. The designed questionnaires were administered through face-to-face interviews.Outcome measures Household emergency preparedness was measured with 14 indicators, tapping into the supply of nine emergency necessities (food and water, extra batteries, battery-powered radio, battery-operated torch, first-aid kit, gas mask, fire extinguisher, escape ropes, whistle), coverage of accident insurance, knowledge of local emergency response systems (emergency numbers, exit routes and shelters) and availability of a household evacuation plan. If an individual acted on 9 of the 14 indicators, they were deemed well prepared. Logistic regression models were established to identify predictors of well preparedness based on 3541 returned questionnaires containing no missing values.Results Only 9.9% of households were well prepared for emergencies: 53.6% did not know what to do and 31.6% did not want to think about it. A higher level of preparedness was found in the respondents who have attained higher education (adjusted OR=0.826 compared with the higher level), participated in emergency training activities (adjusted OR=2.299), had better emergency knowledge (adjusted OR=2.043), reported less fate-submissiveness (adjusted OR=1.385) and more self-reliance (adjusted OR=1.349), prior exposure to emergency events (adjusted OR=1.280) and held more positive attitudes towards preparedness (adjusted OR=1.286).Conclusion Household preparedness for emergency events is poor in China. Lack of motivation, negative attitude to preparedness and knowledge shortfall are major but remediable barriers for household preparedness.